Plays from favorite folk tales : 25 one-act dramatizations of stories children love - Kamerman, Sylvia E. (Plays, Inc., 1987)
Twenty-five one-act dramatizations of stories from folklore. Includes "Rapunzel," "Aladdin," "King Midas," "Stone Soup," and "Finn McCool."